Optimalisasi Pendistribusian Garam Guna Meminimasi Biaya Pengiriman (Studi Kasus : PT JMU) - Abdullah, Achmad Naufal Aqil; Herlina, Herlina (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
PT JMU is a manufacturing company in East Java focused on salt production. The salt products produced by PT JMU include various types of salt, including coarse salt, fine salt, and consumption salt. PT JMU utilizes a region-based distribution model in its distribution process. This model results in limitations in the reach of the distribution fleet, leading to high travel distances and distribution costs. To address this issue, further analysis is required using a combination of the saving matrix method with nearest insert. This combination method utilizes distance matrices from the factory to retail and retail to retail. Thus, it can generate optimal total travel distances and distribution costs. The results of this method can reduce travel distance by 237 km and distribution costs by Rp 546.000.